Effect of Contact Time and Adsorbent Dosage on Removal of Copper Ions from Aqueous Solutions by Iron Slag - Ali Elkais; Alburki, Salem (AlQalam Journal of Medical and Applied Sciences, 2025)
This work aims to study the effectiveness of iron slag in removing copper ions from aqueous solutions, depending on different parameters such as contact time, particle diameter, pH, initial concentration, sorbent dosage, and temperature. In this research, some variables such as contact time, dosage, and particle size were studied based on room temperature. The results indicated that the best removal of copper ions was at contact time (90 min), sorbent weight (3.5 g), and sorbent particle size (200 μm). With the initial concentration of the solution, the best removal percentage was 99.55%, and the maximum adsorption capacity was 96.08 mg/g. From these results, it is clear how suitable it is to use iron slag in reliably removing copper ions from wastewater and industrial wastewater.